One substrate, many fates: different ways of methanol utilization in the acetogen Acetobacterium woodii. (11th May 2022) - Litty, Dennis; Kremp, Florian; Müller, Volker
Summary: Acetogenic bacteria such as Acetobacterium woodii use the Wood–Ljungdahl pathway (WLP) for fixation of CO2 and energy conservation. This pathway enables conversion of diverse substrates to the main product of acetogenesis, acetate. Methyl group containing substrates such as methanol or methylated compounds, derived from pectin, are abundant in the environment and a source for CO2 . Methyl groups enter the WLP at the level of methyltetrahydrofolic acid (methyl‐THF). For methyl transfer from methanol to THF a substrate‐specific methyltransferase system is required. In this study, we used genetic methods to identify mtaBC2A (Awo_c22760‐Awo_c22740) as the methanol‐specific methyltransferase system of A . woodii . After methyl transfer, methyl‐THF serves as carbon and/or electron source and the respiratory Rnf complex is required for redox homeostasis if methanol + CO2 is the substrate. Resting cells fed with methanol + CO2, indeed converted methanol to acetate in a 4:3 stoichiometry. When methanol was fed in combination with other electron sources such as H2  + CO2 or CO, methanol was converted Rnf‐independently and the methyl group was condensed with CO to build acetate. When fed in combination with alternative electron sinks such as caffeate methanol was oxidized only and resulting electrons were used for non‐acetogenic growth. These different pathways for the conversion of methyl‐group containing substrates enable acetogens to adapt to various ecological niches and to syntrophic communities.